Réponses

2013-02-08T22:14:02+01:00

Bonsoir

f est une fonction affinede type f(x) = ax+b

a)

f(0) = 5                    et                                f(2) =3

a(0) + b = 5            et                           2a+b =3 

b =5    on remplace dans la seconde  2a+5 =3 

                                                                     a = -2/2 = -1

f(x) = -x + 5

 

b)

f(-2) = 1                      et                            f(3) = 6 

-2a+b = 1                   et                              3a+b = 6 

b = 1+2a                    alors                    3a +2a+1 =6 

                                                                  5a = 5

                                                                   a =5/5 = 1

b = 1+2(1) = 3

 

f(x) = x + 3